The Municipality's Commitment to Primary Health Care and Access to Medicinal Cannabis-Based Medications: The Case of Goiânia (CIPEEX, 2023)
It is the duty of the State to ensure access to healthcare for the population, providing quality medical services, implementing preventive public policies, and promoting an environment conducive to the well- being of the population. In this context, the present work addresses the commitment of the municipality of Goiânia, a pioneer in the municipal law that mandates the municipal provision of medicinal cannabis- based medications. It also discusses the growing demand for these medications, the increase in legal proceedings, and the benefits of phytotherapeutic treatments with cannabis compared to allopathic ones. Furthermore, it explores the pharmaceutical and economic advantages and the economic viability for the municipality, as well as the prospect of including these treatments in the Farmácia Viva programs, provided there is federal regulation allowing the cultivation and handling of cannabis for medicinal and industrial purposes. Finally, it highlights the importance of building a Municipal Reference Center for Medicinal Cannabis (CRMCM) and the administrative, financial, and political challenges involved in this process.